2013
DOI: 10.1371/journal.pone.0069168
|View full text |Cite
|
Sign up to set email alerts
|

De novo Assembly and Characterization of the Barnyardgrass (Echinochloa crus-galli) Transcriptome Using Next-Generation Pyrosequencing

Abstract: BackgroundBarnyardgrass (Echinochloa crus-galli) is an important weed that is a menace to rice cultivation and production. Rapid evolution of herbicide resistance in this weed makes it one of the most difficult to manage using herbicides. Since genome-wide sequence data for barnyardgrass is limited, we sequenced the transcriptomes of susceptible and resistant barnyardgrass biotypes using the 454 GS-FLX platform.Results454 pyrosequencing generated 371,281 raw reads with an average length of 341.8 bp, which made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 36 publications
5
61
0
Order By: Relevance
“…GS FLX+ sequencing has been successfully used for de novo assembly of transcriptomes in many species [26]-[36]. In common with other recent studies, our results indicated that the GS FLX platform can provide much more data than the traditional Sanger sequencing method.…”
Section: Resultssupporting
confidence: 83%
“…GS FLX+ sequencing has been successfully used for de novo assembly of transcriptomes in many species [26]-[36]. In common with other recent studies, our results indicated that the GS FLX platform can provide much more data than the traditional Sanger sequencing method.…”
Section: Resultssupporting
confidence: 83%
“…29,056 [23], 60,765 [20], 65,340 [21], 79,082 [22]). 35,016 unigenes were annotated by nr database from 100,742 unigenes.…”
Section: Discussionmentioning
confidence: 99%
“…Barnyardgrass ( E. crus-galli ) seeds from herbicide-susceptible (S) or -resistant (R) biotypes were processed as previously described [2]. For iTRAQ experiments and functional analysis, a flow chart related to the associated research article [1] was shown in Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%